Carrion Crows Cannot Overcome Impulsive Choice in a Quantitative Exchange Task - Bugnyar, Thomas; Wascher, Claudia A.; Dufour, Valerie (Frontiers in Psychology, 2012)
The ability to control an immediate impulse for a future, more preferred outcome has long been thought to be a uniquely human feature. However, studies on non-human primates revealed that some monkeys and apes are capable of enduring delays to get a more preferred food and/or more food of the same kind. Recently two corvid species, the common raven (Corvus corax) and carrion crow (Corvus corone corone), exchanged food for a better quality reward, whereas they seemed to have difficulties to do so for a higher quantity. In the present study we specifically investigated carrion crows’ ability to overcome an impulsive choice in a quantitative exchange task. After a short delay, individuals were asked to give back an initial reward (cheese) to the human experimenter in order to receive a higher amount of the same reward (2, 4 or 8 pieces). We successfully tested six captive crows. Three individuals never exchanged one piece of cheese against a higher quantity; the other three birds did exchange at very low rates. In order to rule out, that crows’ poor performance is due to the fact that they cannot discriminate between different quantities or that they do not attribute a higher value to higher quantities, we performed a preference test between one and more pieces of cheese. All birds chose the higher quantities significantly more often, indicating that they can discriminate between quantities and that higher quantities actually have a value for them. Taken together, these results suggest that, although crows may possess the cognitive abilities to judge quantities and to overcome an impulsive choice, they do so only in order to optimize the qualitative but not quantitative output in the exchange paradigm.